Methicillin-sensitive Staphylococcusaureus bacterial endarteritis associated with vascular closure device. Issue 1 (19th January 2020) - Alves, Rosa; Judas, Tiago; Vieira, João Valença; Delerue, Francisca
Abstract : Percutaneous endovascular procedures (PEPs) are increasingly common in clinical practice. Percutaneous closure devices (PCD) ensure safe and immediate haemostasis, reducing the length of hospitalisation and improving patient comfort. Infectious complications are rare. We present the case of a 65-year-old man who was admitted to hospital because of fever and weight loss. He had a history of carotid arterial disease, having been submitted to a PEP 3 weeks before. On admission, he presented feverishly. Anaemia and elevated inflammatory parameters were detected on basic chemistry. Blood cultures isolated methicillin-sensitive Staphylococcus aureus and antibiotic therapy was started. He maintained fever and developed signs of right lower limb ischemia. Bacterial endocarditis was ruled out. Positron emission tomography (PET)-scan revealed inflammatory activity involving the right femoral artery (RFA). Bacterial femoral endarteritis was confirmed on surgical exploration, which documented the presence of infected PCD and occlusion of RFA. After surgery, apyrexia and improvement of ischaemic signs were achieved.